European study on the attitude of psychiatrists towards their patients. (13th April 2021) - Ori, D.; Szocsics, P.; Molnar, T.; Guevara, K.; Bankovska-Motlova, L.; Ivanovic, I.; Carbone, E.A.; Kotsis, K.; Dashi, E.; Ahmadova, G.; Panayi, A.; Kafali, H. Yilmaz; et al.
Abstract : Introduction: Many people think that people with mental disorders might be dangerous or unpredictable. These patients face various sources of disadvantages and experience discrimination in job interviews, in education, and housing. Mental health-related stigma occurs not only within the public community, it is a growing issue among professionals as well. Our study is the first that investigates the stigmatising attitude of psychiatrists across Europe. Objectives: We designed a cross-sectional, observational, multi-centre, international study of 33 European countries to investigate the attitude towards patients among medical specialists and trainees in the field of general adult and child and adolescent psychiatry. Methods: An internet-based, anonymous survey will measure the stigmatising attitude by using the local version of the Opening Minds Stigma Scale for Health Care Providers. Data gathering started in July this year and will continue until December 2020. Results: This study will be the first to describe the stigmatising attitude of psychiatric practitioners across Europe from their perspectives. Conclusions: The study will contribute to knowledge of gaps in stigmatising attitude towards people with mental health problems and will provide with new directions in anti-stigma interventions. Disclosure: No significant relationships.